Congenital arterioportal fistula of the liver with reversal of flow in the superior mesenteric vein - Bakker, J; Robben, S G; Hazebroek, F W; Meradji, M (Pediatric radiology, 1994)
We report on a newborn with a large arterioportal fistula of the liver complicated by a sudden reversal of flow in the portal and superior mesenteric vein, leading to congestion and ischemia of the small intestine. Ultrasound, duplex Doppler sonography and angiographic features are presented. Ligation of the hepatic artery led to a complete recovery.